The incidence and importance of anaemia in patients undergoing cardiac surgery in the UK – the first Association of Cardiothoracic Anaesthetists national audit1. (18th March 2016) - Klein, A. A.; Collier, T. J.; Brar, M. S.; Evans, C.; Hallward, G.; Fletcher, S. N.; Richards, T.; ,
Summary: The importance and variability of pre‐operative anaemia in cardiac surgical patients across the UK is not known, and there is debate about its association with patient outcomes. The Association of Cardiothoracic Anaesthetists carried out its first national audit on anaemia and transfusion, and analysed data from 19, 033 patients operated on in 12 cardiac surgical centres between 2010 and 2012; 5895 (31%) had pre‐operative anaemia. Centre‐specific prevalence of anaemia varied from 23% to 45%; anaemia was associated with older patients, diabetes and surgical risk (EuroSCORE). Nevertheless, controlling for these factors, regional variation remained an independent effect (p < 0.001). Multivariable analysis demonstrated an independent association of anaemia with transfusion (odds ratio (95% confidence interval) 2.75 (2.55–2.95), p < 0.001), mortality (1.42 (1.18–1.71), p < 0.001) and hospital stay (geometric mean ratio (95% confidence interval) 1.15 (1.13–1.17), p < 0.001). Haemoglobin concentration per se was also independently associated with worse outcomes; a 10 g.l −1 decrease in haemoglobin was associated with a 43% increase (95% confidence interval 40–46%) in the odds of transfusion and a 16% increase (95% confidence interval 10–22%) in the odds of mortality (both p < 0.001). This large UK‐wide audit has demonstrated marked regional variation in both anaemia and transfusion, with a consistently high incidence of both. The independent association between pre‐operative anaemia and worse outcomes in UK practice has also been confirmed, and robust prospective study of anaemia treatment before cardiac surgery is required; these data will assist in designing such trials.